A model to discipline autonomy in cyber‐physical systems‐of‐systems and its application. Issue 9 (23rd November 2020) - Gharib, Mohamad; Dias da Silva, Leandro; Ceccarelli, Andrea
Abstract: A cyber‐physical system‐of‐systems (CPSoS) can be defined as a system‐of‐systems (SoS), composed of several operable and autonomous constituent systems (CSs) that are themselves cyber‐physical systems (CPSs). A main challenge in integrating CPSoS to function as a single integrated system is the autonomy of its components, which may result in undesirable, unsecure, or even unsafe situations. In this paper, we advocate that in order to facilitate the integration of CPSs within the overall context of their CPSoS, we may need to adjust their level of autonomy in a way that enables them to perform their activities and avoid undesirable, unsecure, and unsafe situations. Reducing such situations surely contributes to the dependability of the CPSoS. In particular, we propose a novel model‐based approach for modeling and analyzing the autonomy levels of CPSs based on their awareness concerning their operational environment as well as their capability to react in a timely, secure, and safe manner while performing their activities. The model is further described in a UML profile and applied to represent activities for autonomous driving scenarios. Using a driving simulator, we implement such models on a target vehicle, and we show the resulting safety improvement, especially in terms of reduced collisions. Abstract : To facilitate the integration of cyber‐physical systems within the overall context of their system‐of‐systems, it may be necessary to adjust their level of autonomy in a way that enables them to perform their activities and avoid undesirable, unsecure, and unsafe situations. We propose a novel model‐based approach for modeling and analyzing the autonomy levels of cyber‐physical systems based on their awareness concerning their operational environment as well as their capability to react in a timely, secure, and safe manner while performing their activities.